2020
DOI: 10.14238/sp22.3.2020.139-45
|View full text |Cite
|
Sign up to set email alerts
|

Pelayanan Imunisasi Dasar pada Bayi di Bawah Usia 12 Bulan dan Faktor yang Memengaruhi di RSUD Wangaya Kota Denpasar Selama Masa Pandemi COVID-19

Abstract: Latar belakang. Pandemi Coronavirus disease 2019 (COVID-19) merupakan kegawatan internasional di bidang kesehatan masyarakat yang membebani sistem kesehatan dan mengganggu kelangsungan layanan kesehatan rutin termasuk imunisasi dasar. Akibatnya, jumlah anak yang diimunisasi menurun, berisiko terjangkit penyakit yang dapat dicegah dengan imunisasi, dan terjadi kejadian luar biasa di tengah pandemi. Tujuan. Mengetahui kondisi layanan imunisasi dasar pada bayi <12 bulan selama masa pandemi COVID-19 dan faktor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 6 publications
1
5
0
4
Order By: Relevance
“…This is in line with research conducted at the Wangaya Hospital, Denpasar City, the results shown that there is a statistically significant difference between the number of visits to basic immunization services from January to July 2020 and January to July 2019. 14 This is also in line with research conducted by the Ministry of Health, where the results for the January to April 2020 period, 18 provices in Indonesia, the coverage of MR immunization is still low. The decrease in suspected measles cases from January to May 2020 when compared to 2019 decreased by 50,4%.…”
Section: "Our Immunization Recording System Uses a Cohort Book A Help Book With Simpus If We Report Monthly We Use Pws Kipi Form And The supporting
confidence: 81%
“…This is in line with research conducted at the Wangaya Hospital, Denpasar City, the results shown that there is a statistically significant difference between the number of visits to basic immunization services from January to July 2020 and January to July 2019. 14 This is also in line with research conducted by the Ministry of Health, where the results for the January to April 2020 period, 18 provices in Indonesia, the coverage of MR immunization is still low. The decrease in suspected measles cases from January to May 2020 when compared to 2019 decreased by 50,4%.…”
Section: "Our Immunization Recording System Uses a Cohort Book A Help Book With Simpus If We Report Monthly We Use Pws Kipi Form And The supporting
confidence: 81%
“…Patriawati reported downward trend in immunization visits at the UKI Hospital at the beginning of the pandemic (March-May 2020) with the number of visits 6 and 5 immunization services at the children's polyclinic of [12]. In addition, based on Felicia and Suarca's study (2020) the immunization visits in pediatric polyclinic during on January-July 2019 to 2020 significantly decrease in coverage of 21.9-13.1% (p < 0.001) [13]. Chandir et al (2020) compared Karachi routine immunization registry in Pakistan and found that 608,832 children (aged 0-23 months) were immunized within 6 months before the lockdown and only 92,492 out of 701,324 children were immunized during the lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…Lockdown is likely to reduce the transmission of PD3I in society. In the midst of the Covid-19 pandemic, health services are burdened, focused on preventing transmission and handling of Covid-19 cases, plus the implementation of the lockdown system, causing routine health services such as immunization to be disrupted [3].…”
Section: Lockdownmentioning
confidence: 99%
“…This happened because health workers (immunization officers) were diverted to handle Covid-19. Vaccination officers are also concerned about the risk of transmitting Covid-19 that may occur during immunization services [3]. If Covid-19 cases continue to increase, there will be a decrease in health personnel available for immunization services, health facilities used as a place for handling / isolating Covid-19 patients, which will lead to a decrease in immunization services.…”
Section: Health Workersmentioning
confidence: 99%
See 1 more Smart Citation